PIROLISIS SAMPAH PLASTIK POLIPROPILENA: TINJAUAN PENGARUH SUHU PADA REAKTOR PIROLISIS KAPASITAS 1 KG/BATCH - Yoel Pasae; Lyse Bulo; Chrisnovan Lande; Eda Lolo Allo (Publikasi dan UKI Press UKI Toraja., 2020)
The increasing use of plastic makes plastic waste the number one contributor to environmental damage in the world. The type of plastic that is most often found as waste is Polypropylene (PP). One way to overcome this problem is to convert plastic into liquid oil, which can be used for various purposes in the chemical industry or as an alternative fuel. Pyrolysis is a technology commonly used to convert plastics into liquid oil, and can be done by the public. But the availability of pyrolysis reactors that are easy and safe to operate is something that needs attention. In this research, a pyrolysis reactor with a capacity of 1 kg / batch has been modified from a gas cylinder. The pyrolysis process was carried out at 250°C, 275°C, 300°C, 325°C and 350°C with a reaction time of 120 minutes. The results showed that pyrolysis at 350°C can produce the highest yield of 62.56%. Through testing using Gas Chromatograpy-Mass Spectroscopy it is known that the liquid oil obtained consists of several groups of compounds or derivatives from Hexane, Heptane, Isotridecanol, Dodecana, Cyclohexana, Benzene, Pentane, and Octana.